2002
DOI: 10.1183/09031936.02.02632001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of asthma with lipid extract of New Zealand green-lipped mussel: a randomised clinical trial

Abstract: Asthma is a chronic inflammatory disease of the airways mediated, at least in part, by leukotrienes and other lipid mediators. Experimental studies have shown that lipid extract of New Zealand green-lipped mussel,Perna canaliculus, is effective in inhibiting 5′-lipoxygenase and cyclo-oxygenase pathways responsible for production of eicosanoids, including leukotrienes and prostaglandins. The aim of this study was to assess its effect on symptoms, peak expiratory flow (PEF) and hydrogen peroxide (H2O2) in expire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 19 publications
4
79
0
Order By: Relevance
“…PEF has been reported in some studies as a marker for lung function. Emelynov et al showed a significant increase in morning PEF with 8 weeks of supplementation with a low dose of n-3 fatty acids (50 mg EPA + DHA per d) in mild-moderate atopic asthmatics (n 46; aged 18-56 years) (116) . In addition, Surette et al reported a significant improvement in quality of life and asthma management scores (including symptoms) assessed by questionnaires after 3 weeks of supplementation (0·5 g EPA + 0·75 g DHA per d; n 65, mild-moderate asthmatics) (117) .…”
Section: Evidence From N-3 Intervention Trials In Asthmamentioning
confidence: 99%
“…PEF has been reported in some studies as a marker for lung function. Emelynov et al showed a significant increase in morning PEF with 8 weeks of supplementation with a low dose of n-3 fatty acids (50 mg EPA + DHA per d) in mild-moderate atopic asthmatics (n 46; aged 18-56 years) (116) . In addition, Surette et al reported a significant improvement in quality of life and asthma management scores (including symptoms) assessed by questionnaires after 3 weeks of supplementation (0·5 g EPA + 0·75 g DHA per d; n 65, mild-moderate asthmatics) (117) .…”
Section: Evidence From N-3 Intervention Trials In Asthmamentioning
confidence: 99%
“…[67][68][69][70] Increases in dietary and inflammatory cell n-3:n-6 PUFA ratio have been associated with improvements in asthma outcomes. [71][72][73][74][75] Interestingly, a Mediterranean diet higher in n-3 fatty acids and antioxidants appears to protect young children from recurrent wheezing. 76 Obese children on average consume more n-6 dietary PUFAs, have a reduced n-3:n-6 ratio in their diet, 77 and have reduced n-3:n-6 PUFA serum levels compared to similar leans.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…[12][13][14][15] Specifically, n-3 PUFA act to decrease the production of inflammatory eicosanoids, cytokines, reactive oxygen species (ROS) and the expression of inflammatory adhesion molecules. 12 An extract from the New Zealand Green Lipped Mussel (NZGLM; perna canaliculus) known commercially as Lyprinol™, contains high levels of the n-3 PUFA eicosapentaenoic acid (EPA; 20:5) and docosahexaenoic acid (DHA; 22:6), 16 and may therefore have the potential to reduce inflammation in the setting of intestinal mucositis.…”
Section: Research Papermentioning
confidence: 99%